2019
DOI: 10.36709/jb.v4i3.10754
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Menulis Teks Eksposisi Siswa Kelas Viii SMP Negeri 1 Duruka

Abstract: Penelitian ini dilatarbelakangi oleh belum ada peneliti yang melakukan penelitian tentang kemampuan menulis teks eksposisi siswa kelas VIII SMP Negeri 1 Duruka. Masalah dalam penelitian ini ialah bagaimanakah kemampuan siswa kelas VIII SMP Negeri 1 Duruka dalam menulis teks eksposisi?. Penelitian ini bertujuan untuk mendeskripsikan kemampuan menulis teks eksposisi siswa kelas VIII SMP Negeri 1 Duruka. Jenis penelitian yang digunakan tergolong penelitian lapangan. Metode yang digunakan adalah metode deskriptif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…They also found a correlation between reading and writing skills of exposition text. The teachers' statements were in line with the study of (Jultia et al, 2019;Sulastin et al, 2019;Yodeska & Nursaid, 2020). They found that learning to write exposition text could improve the learners' skills to argue, share opinions, think logically, creatively, systematically, and persuasively.…”
Section: Discussionsupporting
confidence: 58%
“…They also found a correlation between reading and writing skills of exposition text. The teachers' statements were in line with the study of (Jultia et al, 2019;Sulastin et al, 2019;Yodeska & Nursaid, 2020). They found that learning to write exposition text could improve the learners' skills to argue, share opinions, think logically, creatively, systematically, and persuasively.…”
Section: Discussionsupporting
confidence: 58%
“…Dalam pendekatan berbasis teks ini, teks tidak diartikan sebagai bentuk bahasa tulis. Teks adalah ungkapan pikiran manusia yang lengkap yang di dalamnya ada situasi dan konteksnya (Salfera, 2017;Trisnoningsih, 2021).Teks dibentuk oleh konteks situasi penggunaan bahasa yang di dalamnya ada ragam bahasa yang melatarbelakangi lahirnya teks tersebut (Jultia et al, 2019;Kormasela et al, 2020;Yusnidar, 2014). Pembelajaran bahasa Indonesia pada kurikulum 2013 menekankan materi pada jenis-jenis teks (genre text) (Fitri & Afnita, 2020;Juariah et al, 2020;Owon, 2019).…”
Section: Pendahuluanunclassified
“…In the 21st century, writing skills greatly influence how well students write in class. Students' writing skills can be improved by writing essays based on factors such as content that is appropriate to the topic, systematic content, correct word choice, sentence effectiveness, and the use of enhanced spelling (EYD), including the use of capital letters and proper punctuation (Jultia et al, 2019;Triyanti et al, 2018). Exercises or practices often carried out in class, and the field can help improve writing skills.…”
Section: Introductionmentioning
confidence: 99%